Incidence and risk factors for limb fracture in greyhound racing in Western Australia - Gibson MJ; Legg KA; Gee EK; Smet A; Medd J; McMullen C; Auld L; Rogers CW (John Wiley and Sons Australia, Ltd on behalf of Australian Veterinary Association, 2024)
Identification of risk factors for race day injury can improve greyhound welfare. Race day fractures are the most significant injury event and have the greatest negative impact on dog welfare and the industry's social license to operate. This study aimed to describe the incidence and risk factors for race-related fractures in greyhounds racing in Western Australia. Electronic extracts describing race level data and race day injuries were provided by Racing and Wagering Western Australia (RWWA). The incidence rate (IR) of fractures for all greyhound race starts in Western Australia from 1 January 2017-31/12/2023 was calculated per 1000 starts. Univariable and multivariable models using Poisson regression were used to calculate the IR ratio of fracture type based on race and greyhound-level factors. There were 198,008 racing starts and 662 (n = 643, 97.1% involving the limbs) fractures resulting in an IR of 3.3 fractures per 1000 starts (95%CI 3.1-3.6). Greyhounds that had an injury in their previous race were 2.3 times (95%CI1.4-4.3) more likely to have a forelimb fracture than greyhounds that did not have an injury (P = 0.013). The risk of tarsal bone fracture was greater in greyhounds older than 30 months and greyhounds that had not raced in the previous 15 days. Risk factors for fractures in the forelimb were associated with trauma after interference or dog collisions, whereas tarsal fractures were associated with strain and cyclic loading from race training/racing. Changes to racing structure, rules and policies based on these risk factors may help to reduce fracture incidence in racing greyhounds.
Keywords: bone fatigue; greyhound racing; injury; musculoskeletal; race day; social license to operate; tarsal bone fracture